Keefektifan Model Pembelajaran Berbasis Literasi untuk Keterampilan Menulis pada Siswa Kelas V Sekolah Dasar - Ambarwati, Wahyu (Jurnal Pancar, 2018)
The purpose of this research is to analyze and describe the effectiveness of literacy-based learning on writing skills of elementary school students. The samples used in this study were fifth grade students of Pajerukan 01 Elementary School, Kalibagor District, Banyumas Regency, totaling 49 students, with 25 students in the control class and 24 students in the experimental class. The experimental design used in this study is quasi. Test the first hypothesis by using independent sample t test, indicating that there are differences in writing skills for fifth grade students between classes that get literacy-based learning and those using conventional learning models, the imitation is shown by the results of calculating 8,460> 1,71 (t count> t table)) and significance value obtained 0.03 <0.05, it can be concluded that Ho1 is rejected and Ha1 is accepted or there are differences in students' writing skills with literacy-based learning and conventional models. Furthermore, the effectiveness test results show that the gain score of the experimental group is greater that is 0.210 while the control group is 0.112.